(3XGgQJG GdJYQja HCd hGdJfcjQ ai GdbQBf GdcQje (B: s (3OQGSI JQcjHjI HdGZjI (B/ s - (3jGSQ MSf eMeO jhSa s; (3YHO GdMejO GdSjhQi (B: s ((3GdbGgQI (B: s (3jGSQ MSf eMeO jhSa (B: s, 2017)
(3JONd gPg GdOGQSI Vef GdOQGSGJ GdfMhjI hGddZhjI hGdOdGdjI GdeQJHWI HGdbQBf GdcQje hgi PGJ Tbjf Tb Ghd jbhe Ydi eMGhdI OQGSI XGgQJi GdJYQja hGdJfcjQ JCUjdG ai GdeDdaGJ GdYQHjI hGdeJQLeI Gdi GdYQHjI GeG GdTb GdGNQ ajeKd GdLhGfH GdJWHjbjI ef NdGd ehGVY Gh feGPL GSejI eQJHWI HGdXGgQJjf ai GdbQBf GdcQje hGYJeO ai Pdc Ydi GdeUGOQ hGdeQGLY GdfMhjI hGdJaSjQjI hGdHdGZjI GdJi OQSJ hagQSJ hMddJ GdfU GdbQBfi GdTQja HefGgLgG GdeJfhYI hGSGdjHgG GdeNJdaI ef GdbOje Gdi GdMLjKs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GddZI GdYQHjI hBOGHgG s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJYQja s; (3GdJfcjQs; (3GdbQBf GdcQje s